A note on a separating system of rational invariants for finite dimensional generic algebras - Bekbaev, Ural (IOP Publishing, 2018)
The paper deals with a construction of a separating system of rational invariants for finite dimensional generic algebras. In the process of dealing an approach to a rough classification of finite dimensional algebras is offered by attaching them some quadratic forms.